2017
DOI: 10.1182/blood-2016-08-736041
|View full text |Cite
|
Sign up to set email alerts
|

Optimized depletion of chimeric antigen receptor T cells in murine xenograft models of human acute myeloid leukemia

Abstract: We and others previously reported potent antileukemia efficacy of CD123-redirected chimeric antigen receptor (CAR) T cells in preclinical human acute myeloid leukemia (AML) models at the cost of severe hematologic toxicity. This observation raises concern for potential myeloablation in patients with AML treated with CD123-redirected CAR T cells and mandates novel approaches for toxicity mitigation. We hypothesized that CAR T-cell depletion with optimal timing after AML eradication would preserve leukemia remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 56 publications
1
130
0
1
Order By: Relevance
“…(70–72). If the predicted CART123 myelotoxicity is confirmed in ongoing trials, we propose that CART123 could be depleted once remission is obtained (using clinically available anti-T cell antibodies) (73) prior to a subsequent stem cell transplant. Since SCT is already a standard strategy for r/r HL and metabolic remission prior to SCT is an important prognostic factor, it may be possible to use adoptive cellular therapy with potent CART123 to achieve a complete remission prior to salvage SCT.…”
Section: Discussionmentioning
confidence: 99%
“…(70–72). If the predicted CART123 myelotoxicity is confirmed in ongoing trials, we propose that CART123 could be depleted once remission is obtained (using clinically available anti-T cell antibodies) (73) prior to a subsequent stem cell transplant. Since SCT is already a standard strategy for r/r HL and metabolic remission prior to SCT is an important prognostic factor, it may be possible to use adoptive cellular therapy with potent CART123 to achieve a complete remission prior to salvage SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Other than CD33, which is expressed on malignant cells and healthy haematopoietic stem cells [46], CD123 expression is increased in malignant haematological cells but rather low on haematopoietic stem cells [47]. Despite the favourable expression profile of CD123, T cells expressing CD123-guided CARs were shown to induce severe haematological off-target toxicities in AML mouse models [48, 49]. For further studies, strategies to either eradicate CAR-modified T cells from the periphery or to transiently express CARs are urgently needed.…”
Section: Therapeutic Nk Cells In the Treatment Of Amlmentioning
confidence: 99%
“…Their data supports that infusion of the anti-CD20 antibody, rituximab, an approved antibody for in vivo therapeutic applications, results in efficient, specific elimination of CD20-positive T lymphocytes through ADCC [205,206,218]. Studies have also demonstrated that rituximab can eliminate CD20positive cells in vivo through inducing complementdependent cytotoxicity, a rapid and efficient mode of cell death [219]. CD20 co-expression with a CD123-CAR demonstrated strong and rapid anti-leukemia activity in a human AML mouse model.…”
Section: Suicide Genes and Safety Switchesmentioning
confidence: 62%